Longhorned beetles (Coleoptera: Cerambycidae) of southeastern Mongolia with particular emphasis on the genus Anoplistes Audinet-Serville, 1833 (Cerambycinae: Trachyderini) - Karpiński, Lech; Enkhnasan, Davaadorj; Boldgiv, Bazartseren; Kruszelnicki, Lech; Iderzorig, Badamnyambuu; Gantulga, Temerlen; Dorjsuren, Altanchimeg; Szczepański, Wojciech T. (Zootaxa, 2021)
New data on the distribution, bionomy, and taxonomy of the longhorned beetles that occur in the poorly studied region of southeastern Mongolia (Ömnögovi, Dornogovi, and Sükhbaatar aimags) are presented together with a list of all taxa that are known from this area. The literature records for all known species from this area were summarized, verified, and mapped. Chlorophorus caragana Xie & Wang, 2012 is recorded from Mongolia for the first time. New localities of some little-known taxa that are endemic to Mongolia and adjacent territories, such as Anoplistes halodendri minutus Hammarström, 1892, Anoplistes kaszabi Karpiński, 2020, and Eodorcadion gorbunovi Danilevsky, 2004 are given. High-quality stacked images of several unique species, e.g., Anoplistes gobiensis (Namkhaidorzh, 1973), Ch. caragana, and Chlorophorus obliteratus (Ganglbauer, 1889) are presented for the first time along with photographs of their habitats. New remarks on highly complex taxonomic issues concerning some species in the genera Anoplistes, Chlorophorus, and Eodorcadion are also provided.